2000
DOI: 10.1182/blood.v95.9.2875.009k12_2875_2882
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti-estrogens inhibit the functional differentiation of human monocyte-derived dendritic cells

Abstract: Dendritic cells (DC) are professional antigen-presenting cells with a unique capacity to initiate and regulate immune responses. Immature CD1a+ DC can be cultured from CD14+monocytes in the presence of interleukin (IL)-4 and granulocyte macrophage colony-stimulating factor in vitro. Results of this study show that the nonsteroidal anti-estrogens toremifene and tamoxifen inhibit this differentiation. In the presence of anti-estrogens the cells lose CD14 expression, but remain CD1a− and clearly have less dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 47 publications
4
59
1
Order By: Relevance
“…DC, which suggests other drugs can be employed to modify DC for treatment of autoimmune disorders [44,45]. In evaluating immunosuppressants, Dex, rapamycin and FK506, commonly used in clinical practice for developing tolerogenic DC, in line with the previous studies [25,26], we found that Dex induced development of CD1a -DC derived from human peripheral monocytes (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…DC, which suggests other drugs can be employed to modify DC for treatment of autoimmune disorders [44,45]. In evaluating immunosuppressants, Dex, rapamycin and FK506, commonly used in clinical practice for developing tolerogenic DC, in line with the previous studies [25,26], we found that Dex induced development of CD1a -DC derived from human peripheral monocytes (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The endocrine system participates in regulating the differentiation and maturation of different DC subtypes, e.g., thyroid-stimulating hormone induces a stimulatory effect on phagocytosis and cytokine production in murine DCs (47). In addition, mRNAs for estrogen receptor-␣ and -␤ have been demonstrated in CD14 ϩ monocytes, cultured immature CD1a ϩ cells, and mature CD83 ϩ cells (48). In culture, bone marrow progenitors give rise to the generation of DCs (49), which can be influenced by the action of androgens and estrogens (48,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mRNAs for estrogen receptor-␣ and -␤ have been demonstrated in CD14 ϩ monocytes, cultured immature CD1a ϩ cells, and mature CD83 ϩ cells (48). In culture, bone marrow progenitors give rise to the generation of DCs (49), which can be influenced by the action of androgens and estrogens (48,50). Moreover, glucocorticoids inhibit the in vitro differentiation of DCs from their progenitors and impair their capacity to undergo terminal differentiation or generate proinflammatory cytokines (17).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The possibility of modulating DC function with certain SERMs has also been evaluated. The antiestrogens tamoxifen and toremifene 44,45 as well as raloxifene 27 are able to inhibit the differentiation and maturation of DCs. While this capacity could possibly be exploited in the treatment of autoimmune diseases it might, on the other hand, interfere with useful immune responses in association with breast cancer treatment or prevention of osteoporosis with tamoxifen or toremifene 44,45 and raloxifene, respectively.…”
Section: Regulation Of Cells Of the Monocyte-macrophage System With Smentioning
confidence: 99%